A Comparative Study of Thyroid Cytology Reporting by Bethesda System and Routine Cytology in a Teaching Institute of Sub Himalayan Region - Mahata, Nirmalesh; Chakrabarti, Indranil (Annals of Pathology and Laboratory Medicine, 2018)
Introduction: Fine needle aspiration cytology (FNAC) is an important preoperative diagnostic tool for thyroid lesions which are endemic in the Sub-Himalayan belt. But sometimes, the FNAC procedures are unable to guide clinicians for definite management. Bethesda System for Reporting Thyroid Cytology (BSRTC) has been formulated to be more sensitive and specific than routine cytological examination in diagnosis of thyroid swellings and act a better tool than the latter due to its objectivity. It may, thus, improve the clinical management of thyroid diseases and even may prevent unnecessary thyroidectomy. Aims and Objective: The study is aimed to compare the interpretation of thyroid FNAC smears by conventional reporting and by BSRTC in patients of thyroid swellings in the Sub-Himalayan regions. Material and Methods: This observational study was done at the Department of Pathology from July 2015 to June 2016. Total 145 cases of thyroid swellings were included for study and reported by both BSRTC and conventional (routine) reporting system. Each of the reporting system was correlated with the available histopathological findings and statistical assessments were performed. Results: Among the total 145 cases, colloid nodules followed by thyroiditis were most common benign conditions in both the reporting systems and among the malignancies; papillary carcinoma was the most predominant. Statistical assessment showed that sensitivity, specificity as well as positive and negative predictive values was higher in BSRTC compared to the conventional reporting system. Conclusion: BSRTC is more accurate than conventional reporting system for thyroid cytology and its management strategy can help to prevent unnecessary thyroidectomy.